Hak Anggota TVI Express berdasarkan Perspektif Perlindungan Konsumen - Andi Arfyan Priatama Amar (CV. Social Politic Genius (SIGn), 2021)
This study aims to determine that TVI Express members get rights as consumers based on the perspective of consumer protection. This type of research is empirical legal research. The interview method was used to obtain research data. The data obtained in this study were then analyzed qualitatively. The results show that TVI Express members do not get rights as consumers based on the perspective of consumer protection. The rights that TVI Express members do not obtain are the right to correct, transparent, and honest information regarding the conditions and guarantees of TVI Express products. In addition, TVI Express members did not get the right to have their opinions and complaints heard on TVI Express service products that could not be used. Furthermore, TVI Express members do not get the right to obtain compensation or replacement from TVI Express. Therefore, it is recommended that legal certainty on consumer protection for TVI Express members can be realized. In this case, practical steps are needed from the government, especially BPSK, to take firm action against TVI Express business actors. In addition, it takes an active role from the community to continue to provide information and complaints if they feel the MLM business has harmed them. In this case, the government, especially BPSK, can suppress the MLM business to be responsible to its members and consumers.